A new test suite reduction method for wearable embedded software. (July 2017) - Shen, Qing; Jiang, Yunliang; Lou, Jungang
Abstract: The verification of wearable embedded software trustability plays a prominent role in the research of wearable embedded technology. Software testing is an alternative way by which to improve the trustability of embedded software systems. The test suites developed are often reused because of the frequent version updates of wearable embedded software; as a result, many test cases in the test suite become redundant. In this paper, a new Boolean subtraction operation is proposed, one that does not alter the coverage of test requirements by the test suites. Redundant requirements and cases are reduced by a column–row transformation operation through the newly defined operation, and the interrelation among the testing requirements and test cases is taken into consideration. The results of experiments on some wearable embedded software test suite reduction indicate that the proposed method results in improved properties compared with H, GE, GRE, and can generate a minimal test suite with which all test requirements can be sufficiently tested.